Optimalisasi Pengelolaan Keuangan dan Pemasaran Digital untuk Meningkatkan Produksi dan Penjualan Dupa di Toko Dupa Ganesha Galang Jaya, Ketewel - Pramuki, Ni Made Wisni Arie Pramuki; Kusumawati, Ni Putu Ayu; Yuliantari, Ni Putu Yeni; Suputra, Gusti Alit (Jurnal Pengabdian Masyarakat Akademisi, 2025)
This community service aims to improve the effectiveness of financial management and digital marketing at the Ganesha Galang Jaya Incense Store in Ketewel, which also produces incense independently. By optimizing the preparation of more structured financial reports that are integrated with the production process, as well as implementing targeted and innovative digital marketing strategies, it is hoped that this micro-business can significantly increase production volume and expand its online sales network, both in local and national markets. Community service activities include intensive training in preparing financial reports, mentoring in the use of various digital platforms for marketing, and continuous evaluation and monitoring of results to support the sustainability and competitiveness of businesses in the digital era. With this approach, community service is expected to strengthen the capabilities of business actors in managing financial and marketing aspects in a professional, modern, and adaptive manner to technological developments.